The Influence Of Attractiveness And Customer Reviews On Visit Decisions Through Visit Interest - Setianingsih, Putri Ayu; Kurniawan, Bayu; Putri, Noventia Karina (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Lawang Sewu is a historic building in the city of Semarang. The aim of this research is to determine the influence of attractiveness and customer reviews on the decision to visit through direct and indirect interest in visiting. This type of research uses accelerated sampling with a quantitative approach. Data were analyzed using Smart PLS 0.3. The population in this study is the unknown number of visitors to Lawang Sewu, so using the Hait et al (2020) formula, the results obtained were 100 respondents. Research Results: (1) attractiveness has a significant effect on interest in visiting (2) customer reviews have a significant effect on interest in visiting (3) attractiveness has no significant effect on the decision to visit (4) customer reviews have a significant effect on the decision to visit (5) interest in visiting has an influence on the decision to visit (6) attractiveness has a significant influence on the decision to visit through interest in visiting (7) customer reviews have a significant influence on the decision to visit through interest in visiting.